1999
DOI: 10.1128/iai.67.3.1238-1244.1999
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Myosin Immunoanalogue with Cell Envelopes of Aspergillus fumigatus Conidia and Its Participation in Swelling and Germination

Abstract: A myosin immunoanalogue was identified in conidia ofAspergillus fumigatus by Western blotting, indirect immunofluorescence assay, and gold immunoelectron microscopy with two different antimyosin antibodies. The distribution pattern of this protein was followed during the early stages of germination. A single 180-kDa polypeptide, detected predominantly in a cell envelope extract, was found to cross-react with monoclonal and polyclonal antibodies raised against vertebrate muscle myosin. Immunoelectron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In yeast cells, wall remodeling for vesicle passage could be facilitated during budding, when the cell wall is thinner in the bud than in nondividing areas of the cell surface (Linnemans et al 1977). Finally, a myosin analog was described as a cell wall component of Aspergillus fumigatus (Esnault et al 1999). In the cytosolic space, motor proteins like myosin and dynein contribute with the movement of transport vesicles (Schliwa and Woehlke, 2003).…”
Section: Putative Mechanisms Of Vesicle Diversity Biogenesis and Pasmentioning
confidence: 99%
“…In yeast cells, wall remodeling for vesicle passage could be facilitated during budding, when the cell wall is thinner in the bud than in nondividing areas of the cell surface (Linnemans et al 1977). Finally, a myosin analog was described as a cell wall component of Aspergillus fumigatus (Esnault et al 1999). In the cytosolic space, motor proteins like myosin and dynein contribute with the movement of transport vesicles (Schliwa and Woehlke, 2003).…”
Section: Putative Mechanisms Of Vesicle Diversity Biogenesis and Pasmentioning
confidence: 99%
“…Myosins or myosin homologues have been identified and/or immunolocalized in numerous tip‐growing cells (fungi and oomycetes, Turian, 1988; Kaminskyj & Heath, 1996; May et al ., 1998; Esnault et al ., 1999: pollen tubes, Heslop‐Harrison & Heslop‐Harrison, 1989b; Kohno et al ., 1992; Terasaka & Niitsu, 1994; Yokota & Shimmen, 1994; Miller et al ., 1995; Yokota et al ., 1995; Cai et al ., 1997; Ren et al ., 1998: algal rhizoids, Braun, 1996). Immunolocalization denoted that myosin is present preferentially in the apical cytoplasm of hyphae (Turian, 1988; Esnault et al ., 1999) and pollen tubes (Yokota et al ., 1995; Pierson & Cresti, 1992), often associated with cytoplasmic organelles and vesicles. In pollen tubes and algal rhizoids different classes of myosin have been identified, leading to the suggestion that different types of organelle might move with the help of different types of myosin, thus exhibiting distinct characteristics of movement (Miller et al ., 1995; Braun, 1996; Cai et al ., 1997).…”
Section: Function Of the Cytoskeletonmentioning
confidence: 99%
“…Inhibition of myosin ATPase activity indicated that tip growth processes, which involve the actin cytoskeleton, also require myosin activity (May et al ., 1998; Steinberg & McIntosh, 1998). In Aspergillus fumigatus myosin inhibition was even more effective than actin inhibition on bulge formation and germination, thus demonstrating its important role in these processes (Esnault et al ., 1999). The ATPase activity of myosins seems to be positively related to the growth rate of tip‐growing cells, as shown in pollen tubes of Lilium davidii (Ren et al ., 1998).…”
Section: Function Of the Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Streinberg et al evaluated the effects of BDM on the morphological characteristics of Saccharomyces species and indicated a gradual reduction in the formation and growth of colonies on Agar medium at 1-30 lm BDM concentrations (Steinberg and McIntosh 1998). In another study by Esnault et al, BDM decreased inflation and budding capability of Aspergillus Fumigatus species and led to impaired cell wall disruption (Esnault et al 1999). Furthermore, Schmidt and Wetzel et al showed that the motility and invasion of Cryptosporidium Parvum were hindered by Cytochalasin D and BDM, respectively (Wetzel et al 2005).…”
Section: Helamentioning
confidence: 99%